The trypanotolerance network. 2. A study on health and productivity of N'Dama, Nguni and their crosses under quantified levels of tsetse challenge in Gabon. 2.2. - The influence of trypanosomiasis on the health status and performance - Paling, R.W.; Leak, S.G.A.; Maehl, H.M.; Jeannin, P.; Yangari, G. (OAU/STRC, 1985)
Presents two different methods of treatment of trypanosomiasis, prophylaxis and therapeutic treatments, for N'Dama cattle, Nguni cattle and their crosses in Gabon; monitors the recording of packed cell volume percent (PCV), trypanosome detection and bodyweight estimation; and studies animal health and reproduction parameters.